2021
DOI: 10.21741/9781644901335-4
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes Involved in Plastic Degradation

Abstract: The global increase in production of plastic and accumulation in the environment is becoming a major concern especially to the aquatic life. This is due to the natural resistance of plastic to both physical and chemical degradation. Lack of biodegradability of plastic polymers is linked to, amongst other factors, the mobility of the polymers in the crystalline part of the polyesters as they are responsible for enzyme interaction. There are significantly few catabolic enzymes that are active in breaking down po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The fungal enzymes involved in PVC biodegradation are currently not well known [178,[214][215][216].…”
Section: Fungal Enzymes Involved In Pvc Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal enzymes involved in PVC biodegradation are currently not well known [178,[214][215][216].…”
Section: Fungal Enzymes Involved In Pvc Biodegradationmentioning
confidence: 99%
“…Although some studies have reported fungi involved in PS biodegradation, research describing fungal enzymes involved in this process are scarce [25,215]. Only an esterase produced by Lentinus tigrinus has been reported to biodegrade PS film into non-toxic smaller molecules [240].…”
Section: Fungal Enzymes Involved In Ps Biodegradationmentioning
confidence: 99%